Work Motivation and Organizational Culture on Work Performance: Organizational Citizenship Behavior (OCB) as Mediating Variable - Widarko, Agus; Anwarodin, M. Khoirul (Golden Ratio of Human Resource Management, 2022)
The purpose of this study was to analyze the effect of work motivation, organizational culture, organizational citizenship behavior on civil servant (ASN) performance.  The sample size is 236 ASN respondents from Blitar Regency, East Java Province, Indonesia. The sampling method used is stratified proportional random sampling, which involves taking samples from the existing area and selecting progressively smaller or larger sizes. After that, it is calculated using Random Sampling using the Slovin Formula. The study stated that motivation directly affects organizational citizenship behavior (OCB). Employees with high intrinsic motivation impact organizational citizenship behavior (OCB) better because they show an attitude of working more than other employees as a form of their perspective of responsibility. Organizational culture has no direct effect on organizational citizenship behavior (OCB). Motivation directly affects performance. ASN performance is directly affected by organizational citizenship behavior. The role of OCB in mediating organizational culture on performance is not fully capable of intervening. The results of this study support the theoretical implications, namely the stronger organizational citizenship behavior (OCB), and supported by good employee work motivation; work behavior will increase. Apart from that, managerially, management can benefit from the results of this study by utilizing a combination of variables.